Broadband metasurfaces for anomalous transmission and spectrum splitting at visible frequencies - Li Zhongyang; Aydin Koray (EPJ Applied Metamaterials, 2015)
The emergent ultrathin metasurfaces are promising optical materials to enable novel photonic functionality and miniature optical devices. By elaborately design the interfacial phase shift from discrete nanoantennas with distinctive geometries, metasurfaces have the potential to shape desired wavefronts and arbitrary steer light propagation. However, the realization of broadband transmission-mode metasurfaces that operates at visible frequencies have still been significant challenging. Because it is difficult to achieve drastic broadband optical response depending on discrete plasmonic resonators and the fabrication of such subwavelength-size resonators with high uniformity is also challenging. Here, we propose an efficient yet a simple transmission-mode metasurface design comprising of a single, quasi-continuous nanoantenna as the build block. Each nanoantenna consist of a trapezoid-shaped triple-layered (Ag-SiO2-Ag) plasmonic resonator which could induce drastic gradient phase shifts for transmitted light. We numerically demonstrated broadband (500–850 nm) anomalous transmitted propagation and spectrum splitting at visible frequencies and beyond. The average power ratio of anomalous transmission mode to the first-order diffraction mode was calculated to be ~1000. Such proposed metasurface design is a clear departure from conventional metasurfaces utilizing multiple discrete resonators, and suggests applications for achieving ultrathin lenses, high SNR spectrometers, directional emitters and spectrum splitting surfaces for photovoltaics.